High-Reliability Teams at Sea: The Role of Psychological Safety, Human–System Interaction, and Workload in Error Reporting Behavior among Offshore Workers - Gomargana, Chrysan; Wibowo, Kevin Aprilio; Widjajakusuma, Jack (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2025)
Offshore oil and gas operations demand high reliability under extreme physical and psychological conditions. Despite robust engineering systems, many accidents still stem from human and organizational factors. This study examines the role of psychological safety, human–system interaction, and workload in predicting error reporting behavior among offshore workers. A quantitative, cross-sectional design was applied using validated self-report scales: the Psychological Safety Scale (Edmondson), System Usability Scale (SUS), NASA Task Load Index (NASA-TLX), and an adapted Error Reporting Behavior Scale. Data were collected from 188 offshore workers in Indonesia through online questionnaires. Multiple linear regression analysis revealed that psychological safety (β = .38, p < .001) and human–system interaction (β = .27, p < .001) significantly and positively predicted error reporting behavior, while workload showed a significant negative effect (β = −.23, p < .001). The model accounted for 36% of the variance in error reporting (R² = .36). These findings indicate that workers are more likely to report errors when they feel safe to speak up, perceive systems as user-friendly, and experience manageable workloads. The study highlights the need for integrated interventions that simultaneously foster psychological safety, ergonomic system design, and balanced workload management to enhance proactive safety behavior in offshore environments. This research contributes to the intersection of industrial–organizational psychology and human factors engineering, emphasizing that safety performance in high-reliability organizations relies on both social and technological resilience. These findings align with Sustainable Development Goal 9 (Industry, Innovation and Infrastructure), reinforcing that resilient and sustainable industrial systems require the integration of human factors into safety management and system design.